Fermentation and blanching as adaptable strategies to improve nutritional and functional properties of unripe Cardaba banana flour - Ayo-Omogie, Helen Nwakego; Jolayemi, Olusola Samuel; Chinma, Chiemela Enyinnaya (Journal of Agriculture and Food Research, 2021)
Poorly emphasized aspect of sustainable food security in developing countries is adoption of indigenous pro cessing technologies. In this context, effects of blanching operation (blanched B, and unblanched, U), fermen tation methods (submerged-liquid, LF and solid-substrate, SF), and time (24, 72 and 120 h) on the physicochemical, pasting, and functional properties of unripe Cardaba banana flours produced with a full factorial experimental design, were investigated. Blanching and fermentation time were significant for pH and the color parameters. There were significant (P < 0.05) reductions in total starch and carbohydrate contents at 17–28% and 13–19%, respectively. Sugar content peaked on the 3rd day of fermentation and declined afterward. All samples experienced a substantial increase in protein with fermentation time (P < 0.01). Both strategies lowered the hydrolysable tannin content of the flours with LF exhibiting 73% and 55% reduction rates for unblanched and blanched samples, respectively. In both fermentation techniques, flours obtained from unblanched banana exhibited higher mineral contents than blanched ones. Similarly, higher values of pasting and functional properties such as setback, breakdown, final and peak viscosities, trough, peak temperature, least gelation, bulk density, and water absorption capacity, characterized BLF, while foaming and emulsion capacity were higher in USF. The study demonstrated the potentials of blanching and fermentation technologies in improving functional food application of unripe Cardaba banana.
Keywords: Cardaba banana; Blanching; Fermentation; Functional and nutritional properties; Sustainability; ACE: Mycotoxin and Food Safety; ACEMFS; Federal University of Technology, Minna; Nigeria